The role of social research in reflexive metagovernance. Theoretical and methodological perspective - Strumińska-Kutra, Marta (Journal of Public Governance, 2013)
The goal of the text is to present theoretical and methodological framework to meet two significant challenges posed against governance and public management theory. Those are: integration of critical perspective and translating theoretical reflection into practice. Focusing on local governance, author proposes research perspective 1) introducing power asymmetries into analysis of governance processes, 2) facilitating reflexion on governance, supporting development of norms of cooperation, triggering social learning processes and therefore enabling alignment of governance theory and practice. Within this framework, the concept of metagovernance, referring to reflexion over governance and intentional design and modification of institutions of governance, is the one of great significance. It opens up a space for implementation of social inquiry linking description, explanation to action.